Natural landscapes as a factor in the effective development of agriculture in the North Caucasus, Russia - S. N. Volkov; S. V. Savinova; E. V. Cherkashina; D. A. Shapovalov; V. V. Bratkov; P. V. Klyushin (Юг России: экология, развитие)
Aim. Assessment of natural landscapes of the North Caucasus in order to increase the efficiency of their use for agriculture on the basis of modern updated data.Material and Methods. Research on the assessment of the state of natural landscapes was carried out by modern methods, including remote sensing using systemic, analytical and comparative geographical analysis methodologies.Results. In agricultural terms, the use of semi‐desert landscapes is limited because a lack of moisture. Accordingly, they are most suitable as pastures (especially in winter), haymaking, and also for the cultivation of melons. Agriculturally flat and hilly warm‐temperate and moderate semi‐arid landscapes are the most favorable landscapes for crop production: the main form of use of these landscapes is as arable land. Lowland temperate semi‐humid landscapes, which are widespread in the North Caucasus foothills, are also quite favorable for agricultural production. Conclusion. We have established that in order to increase the efficiency of use of landscapes of the North Caucasus, high‐quality zoning is necessary with the subsequent development of agro‐reclamation measures.